COUNSELING COMMUNICATION STRATEGY OF GUARDIAN IN IMPROVING THE DISCIPLINE OF STUDENT’S WORSHIP AT PESANTREN AR-RAUDHAH AL-HASANAH MEDAN - Lubis, Darvina (Tawazun: Jurnal Pendidikan Islam, 2018)
The communication strategy of Guardian Counciling Section in improving discipline students worship Pesantren Ar Raudhatul Hasanah Medan. From interviews suggests that the communications strategy undertaken by Guardian Counciling in Pesantren Ar-Raudhatul Hasanah Medan is a technique giving reward and punishment, coercive and persuasive techniques. The diffialties faced by Guardian Counciling in the implementation of communication strategy, according to the results of the study showed that new students were carried away with their old habits before entering the boarding schools, language diffialties, various culture caused a large number of students and also communication message lost because delegations system which is used to convey the message communication to the students through students organization. This complicates Guardian Counciling Section in conducting communications strategy effective. Judging from the communication strategy Guardian Counciling Section Pesantren Ar-Raudhatul Hasanah, it is mostly used the technique reward. Some indications, such as giving gifts, awards and honors for students who are disciplined (reward) and punishment (punishment) to undisciplined. While the views of the effectiveness of its communications strategy, the interviews show that the strategy is quite effective in improving the discipline of worship students. Keywords : counseling, communication strategy, discipline of student’s worship, ar-raudhah al-hasanah.